Willingness to vaccinate and willingness to pay for vaccination against peste des petits ruminants in northern Senegal - Ilboudo, Guy S.; Wanyoike, Francis N.; Bahta, Sirak T.; Sy, S.; Djigo, C.A.T.; Sall, P.A.; Lô, M.M.; Dione, Michel M. (Frontiers Media, 2024)
Background: This study was carried out in Linguere department, Louga region of Senegal. Its objective was to explore the socio-economic factors that influence small ruminant producers’ decisions on vaccination against peste des petits ruminants.